Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids